Longstanding giant frontoethmoidal mucocele with orbital and intracranial extension: challenges of surgical approach in a developing nation - Aliyu, Daniel; Adeyeye, Foluso M.; Mohammed, Adamu D.; Iseh, Kufre R.; Lasseini, Ali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Mucoceles of the paranasal sinuses are expansile, benign mucus filled epithelial lined cystic-like lesion resulting from chronic obstruction to sinus ostia. They erode bony walls by pressure and bony resorption with the frontal and ethmoid sinuses predominately affected. The expansile lesion can involve surrounding structures like the orbit, intracranium or nasopharynx. Diagnosis is based on history, examination and radiological assessment with Computerized tomography scan being the imaging of choice. Surgery is the mainstay of treatment and would require collaboration with the neurosurgeons or the ophthalmologist when it extends to the brain or orbit respectively. It can be done via an external approach, endoscopic approach or a combination of both. If left without intervention, it may cause morbidity and potential mortality due to its proximity to the brain and orbit. We report a rare case in our setting of a 65-year-old male farmer with a painless huge left sided cystic fronto-orbital swelling of 8 years that mimicked a benign orbital tumor. The mass was non-tender and not pulsatile measuring about 20×18 cm with normal visual acuity. Computed tomography (CT) scans of the brain and paranasal sinus revealed a large well-defined non-contrast enhancing homogenous lesion involving the left fronto-ethmoidal sinuses with orbital and intracranial extension as well as inferolateral displacement of the left eye globe. He was reviewed by the ENT surgeons, neurosurgeons and ophthalmologists and subsequently had frontoethmoidectomy via an external approach.